Effect of Workload, Work Stress Management, And Work Motivation On Employee Performance At PDAM Tirta Bukae Luwu Utara - Mardian, Mardian; Anwar, Suhardi M.; Mustafa, Sri wahyuni (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to examine the influence of workload, work stress control, and work motivation on employee performance at PDAM Tirta Bukae, North Luwu Regency. Methodology: Using a quantitative approach, data were collected through questionnaires from 70 employees who formed the total sampling. Data analysis was performed using multiple linear regression using SPSS. Results and Findings: Research shows that work stress management and work motivation have a positive and significant effect on employee performance (p < 0.05), while workload has no significant effect (p > 0.05). These findings emphasize the importance of stress management and increased motivation in boosting work productivity, while disproportionate workload does not directly impact performance. Novelty and Originality: The uniqueness of this study lies in its approach, which simultaneously integrates three key variables within the context of regional public organizations, a topic that has not been widely researched before. Compared with previous studies that generally focused on one or two aspects, this research makes an original contribution to the development of employee performance models in the public service sector. Conclusion: This study shows that work stress management and work motivation have a significant effect on employee performance at PDAM Tirta Bukae, North Luwu, while workload does not have a significant effect. Type of Paper: Empirical Research Articles.